Analisa Lembaran Komposit Berpenguat Serbuk Ijuk Mesh 60 Menggunakan Matrik Karet Alam Dengan Variasi Komposisi Serbuk Ijuk (0, 10, 20) Phr Terhadap Radiasi Sinar Gamma - Faid, Anim Nur, Masyrukan, ST, MT, Joko Sedyono, Ph.D (2016)
This study aims to determine how much influence Composite powder 60 mesh fibers using a matrix of natural rubber against gamma radiation. Powder composition fibers used in this study was the variation (0, 10, 20) phr. Manufacture of composite fiber material begins with the preparation of fibers, latex I 60% radiation and chemicals such as darvan, ZnO, ZDEC, ionol, sulfur for support in the manufacture of composite materials. The initial process of manufacturing fiber into powder made with palm fiber laundering using clean water. Then do the drying in the sun until dry and continue the process of milling, comminution and cutting using a blender to quickly break down into powder. In the manufacture of composite, a chemical used as supporting material dispersion process is carried out beforehand. The dispersion process chemicals such as ZnO, ZDEC and ionol carried out for 24 hours, while sulfur for 48 hours. Mixing of composite materials made on a glass and stirred for 15 minutes and then is poured into a mold with the dimensions specified. Furthermore, the vulcanization process by using an oven with a temperature of 90°C for 1 hour. The higher the powder composition of the fibers used in composite materials, the higher the value the absorption of radiation produced. Values composite absorption of the gamma radiation without particle fibers (0 phr) absorption values obtained by 26.58%, with the weight fraction powder composite fibers 10 phr obtained absorption values of 31.44% and composite powders with a weight fraction of fibers 20 phr absorption values obtained by 32.46%.